Usefulness of 3D hybrid profile order technique with 3T magnetic resonance cholangiography: Comparison of image quality and acquisition time. Issue 5 (30th April 2016) - Yokoyama, Koichi; Nakaura, Takeshi; Iyama, Yuji; Sakamoto, Seiji; Takemura, Atsushi; Okuaki, Tomoyuki; Harada, Kazunori; Yamashita, Yasuyuki
Abstract : Purpose: To evaluate the image quality and acquisition time of magnetic resonance cholangiopancreatography (MRCP) with and without the 3D hybrid profile order technique. Materials and Methods: We studied 32 consecutive patients at 3T. They underwent MRCP with and without the 3D hybrid profile order imaging technique during free breathing and MRCP with the 3D hybrid profile order technique during a single breath‐hold. The image acquisition time was 82% shorter with the 3D hybrid profile order technique than without it. The contrast, signal‐to‐noise‐ratio (SNR), and contrast‐noise‐ratio (CNR) between the common bile duct (CBD) and periductal tissues on 3D‐MRCP were evaluated quantitatively. Results: The contrast, SNR, and CNR of the CBD under free breathing was significantly higher with the 3D hybrid profile order technique than without it ( P < 0.01). The contrast, SNR, and CNR of the CBD under a single breath‐hold was significantly higher with the 3D hybrid profile order technique than without it ( P < 0.01). There were no significant differences in the contrast, SNR, and CNR of the CBD between the 3D hybrid profile order with a single breath‐hold and with free breathing ( P = 0.12, 0.28, 0.28, respectively). Conclusion: Using 3T MRI for MRCP with the 3D hybrid profile order sequence yielded significantly improved contrast and CNR with a shorter image acquisition time without sacrificing image quality when compared to imaging without the 3D hybrid profile order sequence. J. Magn. Reson. Imaging 2016;44:1346–1353.